Efektivitas Project Based Learning Untuk Meningkatkan Keaktifan Dan Tanggung Jawab Siswa Di SMP Negeri 4 Kediri - Elmi Firanda; Nining Solekah; Vivi Rahmawati (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to improve students' activeness and responsibility in the guidance and counseling service process. Initial observations in class IX A of SMP Negeri 4 Kediri showed a serious problem where students tended to be passive and less responsible for the tasks given during the service. To overcome this, the guidance and counseling service in this class was designed innovatively using the Project Based Learning learning model. This approach was chosen because it is able to encourage students to play an active role in completing real projects, so that it can indirectly foster a sense of responsibility. This classroom action research was carried out in two cycles, with a total of three meetings starting from pre-cycle activities followed by cycles 1 and 2. The results of the study showed a significant increase in activeness and responsibility with an average of 50% in the pre-cycle, then 62% in cycle 1 and 74% in cycle 2. This demonstrates the effectiveness of Project Based Learning in improving student activeness and responsibility at SMP Negeri 4 Kediri.